Framework Administered Account for Selected Fund Activities : Government of Canada Subaccount. (Policy Papers; Policy Paper ;, 2012)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for Selected Fund Activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of subaccounts. This paper requests Executive Board approval to establish the Government of Canada Subaccount for Selected Fund Activities (the "Subaccount") under the terms of the SFA Instrumen.